2004
DOI: 10.1002/ejoc.200400192
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Aspects of the Bismuth‐Catalysed Oxidation of Epoxides to α‐Diketones

Abstract: The mechanism of the direct oxidation of 1,2‐disubstituted epoxides to α‐diketones catalysed by BiIII derivatives was examined. The oxidation was carried out in DMSO under dioxygen. Experimental evidence for the various steps of the reaction was obtained from spectroscopic data, isolation of intermediate species, reactions with Bi0, reaction under dinitrogen rather than under dioxygen, measurement of the oxygen consumption, cyclic voltammetry, and oxidations performed in the presence of methyl phenyl sulfoxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…[126][127][128][129][130] It is also important to get a compound which is stable against decomposition. [131,132] The pioneering efforts aimed at solving the toxicity and instability issues in perovskite solar cells using halide double perovskite therefore incorporated the Bi 3+ along with a monovalent cation Ag + in the B-site. [130] The valence band maximum (VBM) of MAPbI 3 is therefore made up of a mixture of the filled 6s 2 and 5p 6 states of Pb 2+ and I − , while the conduction band minimum (CBM) is made up of the vacant 6p state of Pb 2+ .…”
Section: Optoelectronic Properties Of Halide Double Perovskitesmentioning
confidence: 99%
See 1 more Smart Citation
“…[126][127][128][129][130] It is also important to get a compound which is stable against decomposition. [131,132] The pioneering efforts aimed at solving the toxicity and instability issues in perovskite solar cells using halide double perovskite therefore incorporated the Bi 3+ along with a monovalent cation Ag + in the B-site. [130] The valence band maximum (VBM) of MAPbI 3 is therefore made up of a mixture of the filled 6s 2 and 5p 6 states of Pb 2+ and I − , while the conduction band minimum (CBM) is made up of the vacant 6p state of Pb 2+ .…”
Section: Optoelectronic Properties Of Halide Double Perovskitesmentioning
confidence: 99%
“…Apart from Pb 2+ , two other main group metal cations Tl + and Bi 3+ can exhibit the 6s 2 6p 0 electronic configuration. However, only Bi 3+ is known to be nontoxic and has been used in organic reactions as a nontoxic additive . The pioneering efforts aimed at solving the toxicity and instability issues in perovskite solar cells using halide double perovskite therefore incorporated the Bi 3+ along with a monovalent cation Ag + in the B‐site .…”
Section: Optoelectronic Properties Of Halide Double Perovskitesmentioning
confidence: 99%
“…34,35 This interesting phenomenon prompted us to examine the behavior of various metals of low standard reduction potential under these oxidative conditions.…”
Section: Oxidative Dissolution Of Metallic Powders In the Presence Ofmentioning
confidence: 99%
“…During mechanistic studies on the oxidation of internal epoxides by metallic bismuth in the presence of triflic acid, we observed that the bismuth metal powder was totally dissolved in DMSO at 100°C under an atmospheric pressure of O 2 to form bismuth(III) triflate solvated by DMSO (Scheme 3). 34,35 This interesting phenomenon prompted us to examine the behavior of various metals of low standard reduction potential under these oxidative conditions.…”
Section: Oxidative Dissolution Of Metallic Powders In the Presence Of Superacidsmentioning
confidence: 99%
“…[67] Even having the heavy metal status, bismuth and its compounds have attracted organic chemists, due to their relatively non-toxicity, ease of handling and non-corrosive nature. [68] Bismuth analogues promote versatile organic transformations most importantly the oxidation of aziridines [69] and epoxides. [70] They are suitable as mild Lewis acid catalysts for organic transformation.…”
Section: Bi 2 O 3 /Zromentioning
confidence: 99%